Intrametropolitan Variation in Wage Rates: The Case of Atlanta Fast-Food Restaurant Workers - Ihlanfeldt, Keith R.; Young, Madelyn V. (The Review of Economics and Statistics, 1994)
Keith R. Ihlanfeldt, Madelyn V. Young, Intrametropolitan Variation in Wage Rates: The Case of Atlanta Fast-Food Restaurant Workers, The Review of Economics and Statistics, Vol. 76, No. 3 (Aug., 1994), pp. 425-433